Prognostic significance of a comprehensive histological evaluation of reticulin fibrosis, collagen deposition and osteosclerosis in primary myelofibrosis patients. Issue 6 (28th September 2017) - Gianelli, Umberto; Fiori, Stefano; Cattaneo, Daniele; Bossi, Anna; Cortinovis, Ivan; Bonometti, Arturo; Ercoli, Giulia; Bucelli, Cristina; Orofino, Nicola; Bulfamante, Gaetano; Iurlo, Alessandra
Abstract : Aims: To evaluate whether a comprehensive histological evaluation of reticulin fibrosis, collagen deposition and osteosclerosis in bone marrow trephine biopsies (BMBs) of primary myelofibrosis (PMF) patients may have prognostic implications. Methods and results: Reticulin fibrosis, collagen deposition and osteosclerosis were graded from 0 to 3 in a series of 122 baseline BMBs. Then, we assigned to each case a comprehensive score [reticulin, collagen, osteosclerosis (RCO) score, ranging from 0 to 9] that allowed us to distinguish two groups of patients, with low‐grade (RCO score 0–4) and high‐grade (RCO score 5–9) stromal changes. Of 122 patients, 88 displayed a low‐grade and 34 a high‐grade RCO score. The latter was associated more frequently with anaemia, thrombocytopenia, peripheral blood blasts and increased lactate dehydrogenase levels. The RCO score was correlated strictly with overall mortality ( P = 0.013) and International Prognostic Scoring System (IPSS) risk categories, and was able to discriminate the overall survival of both low‐ and high‐grade patients (log‐rank test: P < 0.001). Moreover, it proved to be more accurate than the European Consensus on Grading of Bone Marrow Fibrosis (ECGMF grade) in identifying high‐risk patients with poor prognosis. Finally, a combined analysis of RCO scores and IPSS risk categories in an integrated clinical–pathological evaluation was able to increase the positive predictive value (PPV) for mortality in high‐risk patients. Conclusion: The comprehensive RCO score, obtained by histological evaluation of reticulin fibrosis, collagen deposition and osteosclerosis was prognostically significant and more accurate than ECGMF grade in identifying high‐risk patients and improved PPV when applied in addition to IPSS.